LINGUOCULTURAL REPRESENTATION OF APPEARANCE AND CHARACTER TRAITS IN ENGLISH AND UZBEK PHRASEOLOGICAL UNITS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the linguocultural representation of appearance and character traits in English and Uzbek phraseological units. Phraseological units are viewed as culturally marked linguistic signs that preserve collective experience, moral evaluation and figurative perception of human personality. The study focuses on how external appearance, facial expression, body image and inner qualities are conceptualized through stable expressions in two genetically different languages. The analysis shows that English phraseology often represents character through individual behavioral signs, emotional control and socially visible features, while Uzbek phraseology more actively connects personal qualities with moral purity, social respect, hospitality, modesty and collective judgement. Particular attention is paid to somatic components such as face, eye, heart, tongue and hand, which function as culturally significant symbols. The findings indicate that appearance-based phraseological units do not merely describe physical features; they also encode ethical, emotional and social meanings. The comparative approach reveals both universal metaphoric models and nationally specific linguocultural associations in English and Uzbek phraseology.